Factors Influencing Adherence to Safety Protocols in Ghanaian Industries - Opong-Addoh, M.A. (University of Ghana, 2013)
Background: Safety in the workplace is very important considering the physical, mental, and financial cost of an unsafe environment. A critical component of safety in the work environment is the adherence of workers to the safety protocols designed for their protection. Many factories report accidents in spite of the existence of safety protocols in those factories and one of the causes of accidents is known to be violations of safety procedures. This study, which was carried out in May- June 2013 sought to find out the factors that influence the adherence of the workers to safety protocols in factory workers of Unilever Ghana Limited (as a standard) and four other food and beverage producing companies. Method: A cross sectional quantitative approach was used to determine the knowledge of the respondents on safety protocols. The safety climate of the factories and socio demographic factors influencing adherence to safety protocols was also assessed. The respondents answered a structured questionnaire about adherence to safety protocols, knowledge of safety protocols in the factories, and the safety climate of the factories. Simple random sampling was the sampling method used and the results were analyzed using SPSS version 20 and Stata version 11 software. Results: The results indicate that Females were more likely to adhere to protocols than males (p=0.002). Knowledge positively influences adherence to safety protocols (p<0.001). Safety climate components like co-worker safety, supervisor safety and presence of safety protocols also significantly influence adherence to safety protocols at significant levels of p=0.002, p<0.001 and p=0.019 respectively. Conclusions: The findings indicate that adherence to safety protocols is positively influenced by Knowledge of protocols and safety climate. Adherence to safety protocols can therefore be improved by putting in measures to increase the knowledge and safety climate of the factories.
Thesis (MPH) - University of Ghana, 2013